Productivity Improvement of Motorcycle Headlight Assembly through Line Balancing Using Simulation Modeling: A Case Study - Neungmatcha, Woraya; Boonmee*, Atiwat (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2020)
The purpose of this paper is to increase the efficiency of the production of motorcycle headlights by balancing the assembly line in order to achieve maximum utilization of manpower. Since the motorcycle headlight assembly in question is a new production line, this research can be seen as providing a supportive approach to achieving work full efficiency. It was observed that improvements can be made to the arrangements of the various elements that form the production line. Therefore, the reseachers proposed a solution that incorporates production line balancing and improvements of work techniques. Simulation with the Arena program is used to analyze the results of the current working conditions and these are compared to the various alternative strategies proposed. The results show that the proposed improvements can help to increase the productivity of motorcycle headlight production line (production cycle time reduced by 25.51 % and production capacity increased by 28.36 % compared to the current situation) and involve more efficient use of manpower (the utilization of manpower increased by 13.33 % compared to the exisitng situation). Moreover, this research and the proposed improvements point to further research aimed at better meeting the monthly demands for product of customer. Keywords: Motorcycle headlight; line balancing; work improvement; simulation *Corresponding author: Tel.: (+66)-893956932 Fax: (+66) 343511404 E-mail: fengawbo@ku.ac.th